The role of institutional quality in moderating tax revenue, revenue-sharing funds from natural resources, and government expenditure on inclusive economic growth - Meliza, Meliza; Ulum, Akhmad Samsul (Jurnal Akuntansi dan Auditing Indonesia, 2025)
This study aims to provide empirical evidence regarding the influence of tax revenue, revenue-sharing funds from natural resources, and government expenditure on the inclusive economic growth of district and city governments in Indonesia, and the role of institutional quality in moderating these relationships. This study used panel data, with an observation period of 2019–2023 across 515 district and city governments in Indonesia. A total of 2,575 observations of the final sample data were obtained using a purposive sampling method, and the hypothesis testing used Partial Least Squares Structural Equation Modelling (PLS-SEM). The PLS-SEM analysis revealed that tax revenue and government expenditure move in the same direction as inclusive economic growth in district and city governments in Indonesia. However, revenue-sharing funds from natural resources have a negative impact on inclusive economic growth. Institutional quality successfully moderates the effect of tax revenue mobilisation and government expenditure on inclusive economic growth. However, it fails to moderate the relationship between revenue-sharing funds from natural resources and inclusive economic growth.